Regional core competencies as a basis for entrepreneurship?: The German hop-growing area of the Hallertau - Pechlaner, Harald; Bachinger, M. (I P Publishing, 2014)
Regions feature specific network structures, identities and knowledge. These characteristics resemble social capital, which is recognized as contributing to entrepreneurship and innovation. This study examines whether entrepreneurial advantages, which are generated by social capital in a regional context, exist in a sustainable perspective. According to the competence-based view, sustainable competitive advantages are based on core competencies, which are valuable, rare and transferable to several markets. Therefore, this study examines social capital as a regional core competency and transfers the competence-based view to a regional context. This is achieved on the basis of the Hallertau region, a hop-planting area in Germany. The paper analyses whether network structure, knowledge and identity, as building blocks of social capital, display core competence quality. As such, this study contributes to the discussion on whether an enterprise's regional embeddedness matters with respect to its sustainable competitiveness.